Short-course antidepressant therapy reduces discontinuation syndrome while maintaining treatment efficacy in patients with refractory functional dyspepsia: A randomized controlled trial - Wang, Qian-Qian; Cheng, Li; Wu, Bi-Yu; Xu, Ping; Qiu, Hong-Yi; Wang, Bo; Yan, Xiu-Juan; Chen, Sheng-Liang (Frontiers in Psychiatry, 2022)
Background and objective: Long-course (LC) antidepressants for treatment of disorders of gut-brain interaction, such as refractory functional dyspepsia (rFD), poses patients at risk of antidepressant discontinuation syndrome (ADS). Short-course (SC) therapy of rapid-acting antidepressant may reduce discontinuation syndromes while maintaining efficacy for dyspeptic symptoms. However, the evidence-based research is lacking. This study aims to determine whether SC therapy with antidepressants could decrease the risk of ADS with comparable treatment efficacy to LC therapy in rFD. Methods: This randomized clinical trial with rFD patients was conducted at a tertiary hospital in China. Participants (N = 240) were randomly allocated to receive flupentixol-melitracen (FM) plus omeprazole therapy for 2 (SC group) or 4 (LC group) weeks, respectively. Scores for Leeds Dyspepsia Questionnaire (LDQ), Generalized Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9 for Depression (PHQ-9) were assessed at baseline and every 2 weeks, ending at 4 weeks after treatment. ADS was assessed after drug cessation. Medication possession ratio (MPR) for FM was calculated. Results: The severity and incidence of ADS of patients in SC group were significantly lower than those in LC group (0.60 ± 0.62 vs 1.71 ± 1.58 and 3.64% vs 39.45%; both P < 0.0001). The MPR values for FM were significantly higher in patients of SC group than in LC group (P < 0.0001). Scores for LDQ, GAD-7 and PHQ-9 decreased in patients of both groups, and the symptom improvement in SC group was comparable to that in LC group after treatment. Conclusions: Compared to 4-week FM therapy, the 2-week FM therapy reduces the risk of ADS with noninferior treatment efficacy in patients with rFD.